Sandy shoreline recovery ability after breakwater removal - Chi, Shanhang; Zhang, Chi; Zheng, Jinhai (Frontiers in Marine Science, 2023)
The removal of coastal structures has emerged as an increasingly considered alternative nature-based solution to sandy coastal erosion due to unsuited structure construction. However, its effectiveness remains uncertain because the ability of natural beach recovery is unclear due to little understanding of shoreline response to the structure removal. In this study, we use a recently developed numerical model to explore the sandy shoreline recovery ability after the removal of an attached breakwater. Both recovery duration and recovery ratio are analyzed concerning various breakwater configurations and environmental settings in a simplified and generalized framework. We find that the sandy shoreline has the ability to naturally recover after breakwater removal but with different recovery durations (years to centuries) and recovery ratios (full to partial). A higher shoreline recovery ability (i.e., shorter duration and larger ratio) is related to shorter effective breakwater length, downdrift inclined breakwater direction, lower angle of wave incidence, and greater longshore sediment transport rate. We reveal that the behavior of sand spit evolution, including the extension and split of the sand spit, is the dominant mechanism for distinct shoreline recovery processes. Two simple formulas are finally proposed to preliminarily estimate shoreline recovery ability for practical purposes. The results of the present study provide new insights into coastal morphological resilience to engineering interventions.